2016
DOI: 10.1111/cea.12712
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammatory airway diseases: the central role of the epithelium revisited

Abstract: The respiratory epithelium plays a critical role for the maintenance of airway integrity and defense against inhaled particles. Physical barrier provided by apical junctions and mucociliary clearance clears inhaled pathogens, allergens or toxics, to prevent continuous stimulation of adaptive immune responses. The "chemical barrier", consisting of several anti-microbial factors such as lysozyme and lactoferrin, constitutes another protective mechanism of the mucosae against external aggressions before adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 178 publications
(210 reference statements)
1
71
0
Order By: Relevance
“…Over time, retained sputum can cause mucous plugs and airway obstruction, obliteration, and damage resulting in more advanced bronchiectasis (6,7). These structural abnormalities in small airways allow for mucus stasis, which favors continued chronic infection and the persisted vicious cycle in patient with bronchiectasis (8,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, retained sputum can cause mucous plugs and airway obstruction, obliteration, and damage resulting in more advanced bronchiectasis (6,7). These structural abnormalities in small airways allow for mucus stasis, which favors continued chronic infection and the persisted vicious cycle in patient with bronchiectasis (8,24).…”
Section: Discussionmentioning
confidence: 99%
“…In non-CF bronchiectasis, the epithelium is damaged and has increased susceptibility to injury as compared to normal airway epithelium. Failure of appropriate growth and differentiation of epithelial cells causes persistent mucosal injury (8). Ciliary dyskinesia and mucus over-production weakens clearance of respiratory pathogens from the airway (7).…”
Section: Introductionmentioning
confidence: 99%
“…Besides its role as a selective and highly regulated physical barrier through the establishment of the intercellular apical junctional complexes between neighbouring airway epithelial cells (AECs) [8][9][10][11], airway epithelium also acts as a critical orchestrator of the airway immune response through the secretion of a wide repertoire of molecules, including antimicrobial peptides and proteins (eg, lysozyme, defensins, and protease inhibitors), antioxidants (eg, superoxide dismutase and glutathione), chemokines, and cytokines, in response to environmental stimuli [2,[12][13][14].…”
Section: Airway Epithelium As a Key Player In Orchestrating The Allermentioning
confidence: 99%
“…In addition, IL-1α release by BECs was enhanced in COPD-derived cells by exposure to cigarette smoke extract. Although this in vitro model may not completely recapitulate the in vivo situation, it provides important new insights regarding the signals delivered by airway epithelial cells and regulating mesenchymal cells.There is accumulating evidence that BECs are key cells in frontline defence that directly signal to immune cells, in particular antigen-presenting cells [3,4]. Several previous works identified that BECs shape the immune response engaged by pathogens [5].…”
mentioning
confidence: 99%
“…There is accumulating evidence that BECs are key cells in frontline defence that directly signal to immune cells, in particular antigen-presenting cells [3,4]. Several previous works identified that BECs shape the immune response engaged by pathogens [5].…”
mentioning
confidence: 99%